Atherogenic Factors and Their Epigenetic Relationships - Ana Z. Fernandez; Andrew L. Siebel; Assam El-Osta (International Journal of Vascular Medicine)
Hypercholesterolemia, homocysteine, oxidative stress, and hyperglycemia have been recognized as the major risk factors for atherogenesis. Their impact on the physiology and biochemistry of vascular cells has been widely demonstrated for the last century. However, the recent discovery of the role of epigenetics in human disease has opened up a new field in the study of atherogenic factors. Thus, epigenetic tags in endothelial, smooth muscle, and immune cells seem to be differentially affected by similar atherogenic stimuli. This paper summarizes some recent works on expression of histone-modifying enzymes and DNA methylation directly linked to the presence of risk factors that could lead to the development or prevention of the atherosclerotic process.